Approach to the Development of PKn In Indonesia After the Proclamation of Independence - Siregar, Lathufi Dinah (International Journal of Students Education, 2024)
Citizenship Education (PKn) is a multifaceted field of study with a cross-disciplinary context. Philosophically, PKn has a basic ontology of political science, especially the concept of political democracy for the aspects of duties and rights of citizens (Chreshore: 1886). From this basic ontology, the concept of Civics developed, which literally (in Latin) is civicus, which means citizen in ancient Greek times. Starting from this understanding, it then developed and was academically recognized as the embryo of civic education. In Indonesia, civic education was adapted into Citizenship Education (PKn). Epistemologically, PKn as a field of science is a development of one of the five social studies traditions, namely citizenship transmission (Barr, Barrt, and Shermis: 1978). The social studies tradition has developed rapidly so that it has now become a body of knowledge that has a systemic paradigm containing three domains of citizenship education, namely: academic, curricular, and socio-cultural domains. Civics pragmatically has a socio-pedagogical vision to educate democratic citizens in a broader context, including formal and non-formal education contexts. Civics is one of the subjects that is very important to be taught at all levels of school, especially elementary school. Ruminiati (2007: 1.15) states that Civics lessons are one of the lessons that are directly related to community life and tend to be affective education. However, in the implementation of learning, not a few misinterpret that Civics and Civics are the same thing. In fact, both have different definitions and functions in learning.